2018
DOI: 10.1007/s10856-018-6104-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric spinal deformity with use of recombinant human bone morphogenetic protein-2

Abstract: In pediatric spine surgery nonunion is a challenging issue. Instability may cause neurological impairment and lead to numerous surgeries in order to achieve fusion. The use of rhBMP-2 for pediatric spinal fusion has not been widely reported. In this study, a series of 13 children (14 procedures) that underwent spinal rhBMP-2 application were analyzed in order to measure clinical and radiographic outcome. Therefore, patient data, diagnosis, construct of instrumentation, type of bone graft, quantity of BMP used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…BMP can induce bone formation and irreversibly promote the differentiation of mesenchymal cells into chondrocytes and bone cells [12]. Among all BMP protein families, BMP2 and BMP9 have the strongest osteogenic ability; they can also induce the formation and deposition of calcium phosphate in bone, which is conducive to repairing bone and joint damage [13,14]. e higher the level of BMP2 and BMP9, the better the degree of bone graft fusion and damage repair [15].…”
Section: Discussionmentioning
confidence: 99%
“…BMP can induce bone formation and irreversibly promote the differentiation of mesenchymal cells into chondrocytes and bone cells [12]. Among all BMP protein families, BMP2 and BMP9 have the strongest osteogenic ability; they can also induce the formation and deposition of calcium phosphate in bone, which is conducive to repairing bone and joint damage [13,14]. e higher the level of BMP2 and BMP9, the better the degree of bone graft fusion and damage repair [15].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patients can achieve relatively desirable outcomes after ACDF, but several studies in recent years have reported that many factors affect the prognosis of such patients, and if the surgical segments cannot achieve effective fusion, problems such as loosening of internal fixation will occur and then seriously affect the postoperative recovery. Therefore, selecting the appropriate fusion material is the key to improving the rate of cervical interbody fusion for ACDF [ 4 6 ]. At present, the fusion materials commonly used in practice are mainly the autogenous or alloplastic bone, in which the autogenous bone is limited in extraction and the alloplastic bone may elevate the possibility of ACDF failure, so both of them do not have good application conditions.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, selecting the appropriate fusion material is the key to improving the rate of cervical interbody fusion for ACDF [4][5][6]. At present, the fusion materials commonly used in practice are mainly the autogenous or alloplastic bone, in which the autogenous bone is limited in extraction and the alloplastic bone may elevate the possibility of ACDF failure, so both of them do not have good application conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional surgical method has a low cure rate and can cause many complications. Therefore, whether rhBMP treatment can increase the cure rate and reduce complications has an important impact on the development of spinal surgery ( Meisel et al, 2008 ; Annis et al, 2015 ; Sayama et al, 2015 ; Stiel et al, 2018 ).…”
Section: Clinical Applications Of Bmpsmentioning
confidence: 99%
“…Therefore, it is very important to find a treatment method that can replace ABG or reduce the number or amount of bone grafts. Currently, ABG combined with BMP is used to achieve spinal fusion and has received increasing attention ( Singh et al, 2013 ; Sayama et al, 2015 ; Stiel et al, 2018 ). In one study, 13 children with spinal deformities were treated with rhBMP-2 during spinal fusion, with an average follow-up of 51 months.…”
Section: Clinical Applications Of Bmpsmentioning
confidence: 99%